Know and understand your skills - Harding, Ben (Video Education Australasia, 2004)
Shows the jobseeker how to identify skills acquired not only through education, training and workplace experience but also through everyday life and recreational pursuits. Uses the Mayer competencies as a generic list for the grouping of skills into a usable framework. This process enables the jobseeker to then select and match skills that are relevant to the job being sought